IMPLEMENTASI KEBIJAKAN BANTUAN KEAMANAN DAN KETERTIBAN MASYARAKAT DI KECAMATAN PALU SELATAN - Riskayanti, St. Aisyah Maulidyah (Katalogis, 2013)
The aim of this research was to know the implementation of society security and safety aid policy in palu selatan sub-district. This was a qualitative research. The informant of this research were vellage chief, babinsa, polmas, the member of bamkamdes, and the community. These informants were determined by using purposive sampling technique. Data collection method covered observation, interview, and documentation, while data analysis technique consisted of data reduction, data display, and conclusion. The theory used was taken from edward III dealing with comunication, resources, disposition, and bureaucracy structure. Generally, the result of the research showed that the policy of society security and safety aid in palu selatan sub-district, partycularly in tavanjuka, nunu, palupi, and pengawu had been implemented well. However, the communication done was not good yet, because from the four places of this research field, one place only, palupi, did it well. Moreover, the resources had a good ability in implementing the policy because it did the policy bused on the rule stated. The disposition of the policy, partycularly for tavanjuka, nunu, palupi and pengawu accepted the policy well, due to the purpose of this policy was to give the security and safety for environment. Besides, the conductors of the policy also emphasized the community needs in conducting the policy; whereas, the bureaucracy structure in this policy was implemented according to the rule or the orientation related to bankamdes. Therefore, administration of the policy was suitable with the expectation, or it was based on the rules to be obeyed.